PENGELOLAAN MEDIA SOSIAL YOUTUBE PADA MAJALAH SEDAP SAJI DALAM MENINGKATKAN VIEWERS - Della Paramitha (2021)
ABSTRACT The background of the existence of the Internet as an information center and means of communication media that reaches all over the world. Information spread over the internet very quickly. It is up to date so that there is a gap between conventional media (old media which includes print media (tabloids, magazines, newspapers) and broadcast media (television, radio) with the emergence of new media (new media which includes applications, social media, websites, and social media). others sourced from the internet). The purpose of the study was to describe how the management Sedap Saji was carried out, especially managing the Youtube media channel Sedap Saji, and to find out if there were any obstacles when managing the Youtube social media account Sedap Saji. The theory used is Affective-Cognitive Consistency Theory. The method used is a qualitative method with the type of descriptive research. The results of this study indicate that in managing the Sajian Sedap Youtube channel, based on the explanations of informant 1, informant 2, and informant 3, the researcher concludes that there are 3 stages in managing the Sajian Sedap Youtube channel, namely the first stage is content preparation and content planning, the second stage is content creation, and the third stage is to publish and promote the content that has been created. Keywords : Management of Youtube Social Media in Magazines Sedap Saji in Increasing Viewers.